Arquitetura escolar em consonância com as práticas experimentais no Ensino de Ciências para os Anos Iniciais do Ensino Fundamenta - Deitos , Greyze Maria Palaoro (2022)
School architecture signals education conceptions implicit in the physical structure and has been inserted in a smooth way in researches in the most diverse areas, which tend to discuss the quality of the school buildings aimed at the learning and teaching processes. The studies point to an intrinsic relation between school architecture and the teaching conception employed. In line with the discussion about school architecture, we approach the experimentation in science teaching, which is pointed out as a learning enhancing factor, including for its straightforward relationship with knowledge production. This qualitative research sought to understand the aspects of the school architecture related to the space destined to the experimentation of the early years of elementary school, questioning how research teachers, from strictu sensu postgraduate courses in Science Teaching in public higher education institutions in Paraná, as well as regulars teachers of science in the early years of elementary school, perceive the architectural aspects necessary for the school environment to carry out experimentation in the early years of elementary school. Thus, we seek to know how the research participants position themselves about experimentation and about the space destined to this practice. As an instrument of data collection for the research teachers, we used the questionnaire, answered by sixteen participants. As for the teachers of the early years, we conducted and interview with the participation of eight teachers via the digital platform Google Meet, also responding to the demands of social isolation generated by the pandemic. The research data were analyzed using Textual Discourse Analysis and showed a need to resume the discussion on initial and continuing teacher education, specifically with regard to the experimentation in science teaching, since the misconceptions regarding experimentation in science teaching were still present in the data construction. The relevance of initial and continuing education was also highlighted by the research teachers, when pointing that this training can facilitate the experimentation practice. It was explicit in the construction of data that the structural aspects pertaining to the science laboratory are present in the conception, mainly of the regular teachers, in their comprehension of the space destined for the practice of experimentation. The research teachers, on their turn, manifest a possibility of exploring different spaces in the school environment for this practice; however, they emphasize the need for a basic infrastructure for this space. In general, the data suggest a more traditional conception of education, which directly influences the school architecture, as well as experimentation. It is still explicit a gap between the theoretical reference consulted and the data constructed in the research, whether regarding the conception of education, experimentation or even school architecture, showing the need for further research on this theme.